Packaging waste generation by households: A mixed method study - Basil F.F.A.; Tamyez P.F.M.; Zahari A.R.; Yao L.; Ahmarofi A.A. (Routledge, 2023)
Packaging; Managing waste; Mathematical simulations; Mixed method; Packaging waste; Recovery rate; Recycling behaviors; Sarawak; Semi structured interviews; Total recovery; Waste generation; Recovery